Ultrasound-guided transbronchial biopsy in the diagnosis of fibrosing mediastinitis-associated pulmonary hypertension - Zhang, Yu; Song, Han-Xiang; Qi, Yong-Jia; Sun, Nan-Nan; Huang, Zan-Sheng; Fu, Wan-Lei; Zhang, Jing; Herth, Felix; Fan, Ye (Orphanet journal of rare diseases, 2025)
Background: Fibrosing mediastinitis is a rare benign disease frequently complicated by pulmonary hypertension. A definitive diagnosis for fibrosing mediastinitis-associated pulmonary hypertension (FM-PH) and its etiologies necessitates mediastinal biopsy and subsequent pathological assessment. Endobronchial ultrasound (EBUS)-guided transbronchial mediastinal cryobiopsy is a recently developed technique that provides diagnostic advantages over standard needle biopsy, particularly in benign mediastinal disorders. Nevertheless, their safety and efficacy in diagnosing FM-PH remain elusive. Methods: We retrospectively studied patients with mediastinal lesion and pulmonary vascular compression who underwent both transbronchial needle aspiration and mediastinal cryobiopsy with EBUS guidance. Diagnostic yields of FM-PH and its etiologies, along with procedure-related adverse events, were analyzed. Immunohistochemical study was conducted to identify immunological properties of FM-PH. Results: Of the 529 patients with mediastinal lesions, 80 exhibited pulmonary vessel compression, including 10 who were ultimately diagnosed with FM-PH following mediastinal biopsy and right heart catheterization. Cryobiopsy showed a higher diagnostic yield for FM-PH compared to needle aspiration (100% versus 40%, p = 0.011). Disease etiologies included pneumoconiosis in 5 cases, tuberculosis in 3, and idiopathic FM-PH in the remaining 2. Cryobiopsy appeared to be superior to needle biopsy for etiological diagnosis, although this difference was not statistically significant (80% versus 60%, p = 0.628). Immunohistochemical analyses of cryosamples revealed mixed inflammatory infiltrates of B and T lymphocytes, as well as macrophages, surrounding or within FM-PH lesions. There was no significant bleeding or other complications. Conclusion: Transbronchial mediastinal cryobiopsy might be a safe and effective diagnostic tool for FM-PH, offering valuable information for personalized treatment.